677 Quick, Simple and just as Effective – Comparing PM:L3 Ratio to NELA, P-POSSUM and NSQIP Scores for Emergency Laparotomy. (12th October 2021) - Ming, J Y; Holmes, M; Pockney, P; Gani, J
Abstract: Aim: Multiple tools (NELA, P-POSSUM, ACS-NSQIP) are available to assess mortality risks in patients requiring emergency laparotomy (1–3), but they are time-consuming to perform and have had limited uptake in routine clinical practice in many countries (4) . Simpler measures, including psoas muscle:L3 vertebrae (PM:L3) ratio (5, 6), may be useful alternates. This measure is quick to perform, requiring no special skills or equipment apart from basic CT viewing software. Method: We performed an analysis on all patients in the Hunter Emergency Laparotomy Audit (HELA) database, from January 2016 to December 2017. HELA is a retrospective review of all emergency laparotomy undertaken in a discrete area in NSW, Australia. Patients with an available CT abdomen were included (N = 500/562). A single slice axial CT image at the L3 endplate level was analysed using ImageJ ® software to measure the area of L3 and bilateral psoas muscles. This can be done using normal PACS software in routine practice. Results: PM:L3 ratios in this cohort have a mean of 1.082 (95%CI 1.042-1.122; range 0.141-3.934). PM:L3 ratio is significantly lower (p < 0.00001) in those patients who did not survive beyond 30 days (mean 0.865 [95% CI 0.746-0.984 ]) and 90 days (mean 0.888 [95%CI 0.768-1.008]) compared to patients that survived these periods (30 day mean 1.106 [95% vs. 1.033-1.179], 90 day mean 1.112 [95% CI 1.070-1.154]) . These associations are similar to those calculated by established risk assessment models. Conclusions: PM:L3 ratio is a reliable, quick and easy risk assessment tool to identify high risk patients undergoing emergency laparotomy.